Movement and play as elements that make possible the acquisition of the written code - Rosa Mary,; Jaimes Martínez, Lucy Yamile (Rastros Rostros, 2024)
The research carried out at the Monterredondo Educational Center with the first A and first B grades, began with three observations and a diagnostic workshop that allowed us to see the different attitudes that the children have towards writing; based on this information we offered the institution a pedagogical proposal characterized by movement and play as elements that make possible the acquisition of the written code in a pleasant and productive way.